Maternal Apical Periodontitis Increases Insulin Resistance and Modulates the Antioxidant Defense System in the Gastrocnemius Muscle of Adult Offspring - Tsosura, Thaís Verônica Saori [UNESP]; dos Santos, Rodrigo Martins [UNESP]; Chaves Neto, Antonio Hernandes [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Carnevali, Ana Carolina Nascimento [UNESP]; Mattera, Maria Sara de Lima Coutinho [UNESP]; Belardi, Bianca Elvira [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; da Silva Machado, Nathália Evelyn [UNESP]; Matsushita, Doris Hissako [UNESP] (Elsevier, 2021)
Introduction: Maternal apical periodontitis (AP) is associated with insulin resistance (IR) in adult offspring. Oxidative stress has been linked to IR. This study investigated insulin sensitivity (IS) and oxidative stress in the gastrocnemius muscle (GM) of adult offspring of rats with AP. Methods: Fifteen female Wistar rats were distributed into a control group, a group with 1 tooth with AP, and a group with 4 teeth with AP. Thirty days after AP induction, female rats were mated with healthy male rats. When male offspring reached 75 days of age, glycemia, insulinemia, and IS were determined. In the GM, the oxidative damage products (thiobarbituric acid reactive substances and carbonyl protein) and activities of enzymatic (superoxide dismutase, catalase, and glutathione peroxidase) and nonenzymatic (glutathione and total antioxidant capacity) antioxidants were quantified. Analysis of variance was performed followed by the Tukey post hoc test (P <.05). Results: Maternal AP was associated with decreased IS and changes in antioxidant activities (reduced superoxide dismutase and increased catalase, glutathione peroxidase, and glutathione) and decreased thiobarbituric acid reactive substance concentration in the GM of their adult offspring. However, maternal AP does not appear to affect glycemia, carbonyl protein concentration, and the nonenzymatic total antioxidant capacity in the GM of this offspring. Conclusions: Maternal AP modulates the antioxidant defense system in the GM of their adult offspring, attenuating lipid peroxidation in this tissue. This reflects part of an adaptive response of the offspring to the stimulation of the maternal chronic oral inflammatory process in which the organism acts by decreasing oxidative tissue damage in the postnatal stage. The present study improves knowledge about the impact of maternal oral inflammation on healthy offspring.
Keywords: Apical periodontitis; fetal development; insulin resistance; oxidative stress